2020
DOI: 10.1155/2020/6450352
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of Proteomic Studies in Gestational Diabetes Mellitus

Abstract: Gestational diabetes mellitus is a progressive and complex pregnancy complication, which threatens both maternal and fetal health. It is urgent to screen for specific biomarkers for early diagnosis and precise treatment, as well as to identify key moleculars to better understand the pathogenic mechanisms. In the present review, we comprehensively summarized recent studies of gestational diabetes using mass spectrometry-based proteomic technologies. Focused on the entire experimental design and proteomic result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 87 publications
0
13
0
Order By: Relevance
“…Due to the significant long-term impacts of gestational diabetes on both the mother’s and offspring’s heath, many studies have started to devise predictive methodologies with which to identify those females most at risk [ 39 ]. Such studies have focused on identifying specific biomarkers, such as changes in DNA methylation of specific genes (e.g., SLC16A11 ) [ 40 ], tissue proteome and transcriptome profiling [ 41 ]; elucidating and characterizing the biochemical cargo of extracellular vesicles [ 42 ]; and establishing optimal dietary regimens [ 43 ]. Interestingly, studies have indicated that multiple micronutrient supplementation in women from high-income countries is associated with an increased risk of developing gestational diabetes and fetal overgrowth [ 44 , 45 ].…”
Section: Parental Diet and Obesitymentioning
confidence: 99%
“…Due to the significant long-term impacts of gestational diabetes on both the mother’s and offspring’s heath, many studies have started to devise predictive methodologies with which to identify those females most at risk [ 39 ]. Such studies have focused on identifying specific biomarkers, such as changes in DNA methylation of specific genes (e.g., SLC16A11 ) [ 40 ], tissue proteome and transcriptome profiling [ 41 ]; elucidating and characterizing the biochemical cargo of extracellular vesicles [ 42 ]; and establishing optimal dietary regimens [ 43 ]. Interestingly, studies have indicated that multiple micronutrient supplementation in women from high-income countries is associated with an increased risk of developing gestational diabetes and fetal overgrowth [ 44 , 45 ].…”
Section: Parental Diet and Obesitymentioning
confidence: 99%
“…Proteomic screening in early pregnancy has revealed multiple potential protein markers, including a cluster associated with insulin secretion, binding, resistance, and signaling for later GDM ( 17 , 18 ). Ravnsborg et al have reported that vitronectin, which is also associated with metabolic syndrome outside pregnancy, significantly augments the predictive power of maternal risk factors ( 17 ) and may prove to be a valuable predictor in clinical use.…”
Section: Prediction Of Gdmmentioning
confidence: 99%
“…Ascertaining the metabolic profiles of women at risk for or diagnosed with overt GDM will further shape precision medicine in which complex metabolic profiles are used to correctly identify at-risk women, aid in diagnosis, predict the efficacy of therapies, and individualize treatment. In addition to metabolomics research, ongoing proteomics research in GDM is attempting to discern proteins from various maternal tissues that will enable early and accurate predictions of risk and complications as well as precise diagnoses [ 93 ]. In summary, it is highly likely that research in metabolomics and proteomics will generate profound advancements in treating GDM.…”
Section: Discussionmentioning
confidence: 99%